A representação da sociedade da cidade do Recife pelas páginas da revista A Pilheria nos anos de 1920. - Silva, Silvania Maria da (2019)
Our work deals with a product — inference from research — which has a social character. The manufacturing process is an application (App) developed, called MeLinda, which allows you to participate in an exhibition in a 3D virtual environment. The exhibition is titled A Pilheria: in its covers, pages, lines and photos, which allows the public to interact. In this, the covers of the magazine A Pilheria, a weekly magazine, are presented, through which we can access, to view and also extract via download, the editorial content of the respective copies, held in the online digital collection of the Fundação Joaquim Nabuco (Fundaj)1, located in Recife, Pernambuco. The aforementioned resources are made available through a page on the institution's website2. We took the images recorded on the covers of A Pilheria, a corpus made up of 48 covers, as the research object. Our creation is a technical production, whose main objective is to rescue the collective memory of the city of Recife, through the images published on the covers of A Pilheria, from the collected corpus, through an informational context for construction, preservation and dissemination through the use social information. In the process of developing the study, we used the bibliographic research method. The magazine was edited and published in the city of Recife, our spatial area, and circulated between the years 1921 and 1932. We have the 1920s as a time frame.